Proposal of improved PTS method for STBC MIMO-OFDM systems - Mata, Tanairat; Boonsrimuang, Pornpawit; Boonsrimuang, Pisit; Kobayashi, Hideo (My University, 2010)
This paper proposes a new Partial Transmit Sequence (PTS) method in conjunction with the concurrent algorithm for Space Time Block Code Multiple Input Multiple Output-Orthogonal Frequency Division Multiplexing (STBC MIMO-OFDM) systems. The feature of proposed PTS method is that each cluster is divided into two parts and these two parts employ the different weighting factors to achieve the better Peak to Average Power Ratio (PAPR) with keeping the same size of side information and almost the same size of computational complexity as that for the conventional concurrent PTS method. Copyright © 2010 The Institute of Electronics, Information and Communication Engineers.
Keywords: MIMO-OFDM; OFDM; PAPR; PTS; STBC